Perception of the educational experience of the students at Regional Brunca, Pérez Zeledón campus, under the virtual modality and the use of ICT, during the II semester of 2020 - Ureña-Hernández , Mariam (2022)
The main objective of this article was to investigate the perception of the students of the Pérez Zeledón campus, in relation to their educational experience under the virtual modality implemented by the UNA. The results show that the student population participating in the study positively value the virtual modality with the support of ICT as appropriate in their learning process, which has allowed them to be trained in new technological tools to maintain or conclude their major. In addition, the most used technological tools and resources were the ® Microsoft Office suite, and the online videoconferencing tools such as ® Microsoft Teams, ® Google Meet and ® Zoom that supported the achievement of educational learning in each major. Furthermore, some of the advantages of this modality are saving of money on transportation and development of self-taught skills. In contrast, some of the disadvantages that the students report is the limited access to internet connection and not knowing how to manage between personal, social and educational life.